Penaruh Kurangnya Sarana Prasarana Kantor Terhadap Efektifitas Kinerja Pegawai Di Dinas Perindustrian, Perdagangan, Energi, Dan Sumber Daya Mineral Provinsi Sumatera Utara - Alya Elva Lianda Nasution; Arnida Wahyuni Lubis (FEB Universitas Maritim Semarang, 2023)
Esources such as capital and office infrastructure. Human resources are the most important thing for an institution, because humans have the ability to set goals, collaborate, and work so that planned goals are achieved. Likewise, it is no less important than the office infrastructure in an institution that has a big influence in efforts to increase work efficiency and effectiveness. Therefore, an institution really needs office infrastructure that can be used by employees in carrying out their duties and responsibilities so that administrative activities and other operational activities can run well and smoothly. Office infrastructure is one of the factors that supports the success of an institution in achieving the organization's goals. Office facilities and infrastructure are an important part that need to be prepared ideally and continuously so that they can ensure the smooth running of employee work activities. Considering that office facilities and infrastructure are very important in efforts to facilitate employee work activities, therefore it is necessary to manage adequate facilities and infrastructure. Means are anything that is used as a tool to achieve aims and objectives, means are more indicated for moving objects such as computers and machines. Infrastructure is something that is the main support for the implementation of the process (Business, Development, Project), infrastructure is more indicated for immovable objects such as buildings, space, land. Work effectiveness is a condition that shows the level of success of management activities in achieving goals including quantity work, quality of work, and timeliness in completing work. Effectiveness is often associated with an efficient system, so that the service process takes place effectively, optimally and on time, thereby eliminating the need for overtime work with its implications. The efficiency of work processes, the level of effectiveness of office technology users, and the comfort of the work environment will directly and indirectly influence employee performance in completing assigned tasks. Apart from that, there are also various factors that influence work effectiveness, including: time, tasks, productivity, motivation, work evaluation, supervision, work environment, equipment and facilities. It is logical and appropriate if increasing effectiveness is made one of the government's long-term targets in implementing its strategy. Based on the phenomena presented above, it is clear that the Office of Industry, Trade, Energy and Mineral Resources of North Sumatra Province has not been well managed regarding infrastructure and has not complied with the appropriate regulatory principles. Problems like this should be addressed immediately and maximized so that in the future it can be as good as it should be. If this is resolved, it will certainly create a comfortable and conducive atmosphere so that employees can carry out their work responsibilities well and optimally. Therefore, the researcher was interested and conducted research as a result of an internship, with the title